UMP-UTY shared good practises in research and patent fields - UMP, PNC
In its effort to become a worldclass technology university, Universiti Malaysia Pahang (UMP) will continue to work on its branding strategy in engineering and technology and walking the talk, the university shared its best research good practices and patents in an international seminar and national symposium, ‘Global Competitiveness through Research Supporting Commercial Industry’ in Indonesia.